The gut microbiome: Connecting spatial organization to function - Tropini, Carolina (Cell Host Microbe, 2017)
The first rudimentary evidence that the human body harbors a microbiota hinted at the complexity of host-associated microbial ecosystems. Now, almost 400 years later, a renaissance in the study of microbiota spatial organization, driven by coincident revolutions in imaging and sequencing technologies, is revealing functional relationships between biogeography and health, particularly in the vertebrate gut. In this review, we present our current understanding of principles governing the localization of intestinal bacteria, and spatial relationships between bacteria and their hosts. We further discuss important emerging directions that will enable progressing from the inherently descriptive nature of localization and –omics technologies to provide functional, quantitative, and mechanistic insight into this complex ecosystem.